Mixed race students in college : the ecology of race, identity, and community on campus - Renn, Kristen A. (SUNY series, frontiers in education., 2004)
"Kristen A. Renn offers a new perspective on racial identity in the United States, that of mixed race college students making sense of the paradox of deconstructing racial categories while living on campuses sharply divided by race and ethnicity. Focusing on how peer culture shapes identity in public and private spaces, the book presents the findings of a qualitative research study involving fifty-six undergraduates from a variety of institutions. Renn uses an innovative ecology model to examine campus peer cultures and documents five patterns of multiracial identity that illustrate possibilities for integrating notions of identity construction (and deconstruction) with the highly salient nature of race in higher education. One of the most ambitious scholarly attempts to date to portray the diverse experiences and identities of mixed race college students, the book also discusses implications for higher education practice, policy, theory, and research."--Jacket